Landscape in sight : looking at America - Jackson, John Brinckerhoff, 1909-1996 (Yale University Press, 1997)
"During a long and distinguished career, John Brinckerhoff Jackson (1909-1996) brought about a new understanding and appreciation of the American landscape. Jackson founded Landscape Magazine in 1951, taught at Harvard University and the University of California at Berkeley, and wrote nearly two hundred essays and reviews. This appealing anthology of his most important writings on the American landscape, illustrated with his own sketches and photographs, brings together Jackson's most famous essays, significant but less well known writings, and articles that were originally published unsigned or under various pseudonyms. Jackson also completed a new essay for this volume, "Places for Fun and Games," a few months before his death."--Jacket.